Influence of colour Doppler echocardiography on the ultrasonic assessment of congenital heart disease: a prospective study. Issue 3 (September 1991) - Gnanapragasam, J P; Houston, A B; Doig, W B; Fraser, R; Lilley, S; Murtagh, E; Olafsson, G
Abstract : OBJECTIVE–To evaluate the additional information provided by colour Doppler in the ultrasonic assessment of congenital heart disease. PATIENTS AND METHODS–A prospective study of 215 children (age range 1 day-16 years) presenting with clinical signs of congenital heart disease. RESULTS–Colour Doppler was essential for the diagnosis of an anomalous left coronary artery and altered the management of a patient initially diagnosed as having cardiomyopathy. Colour Doppler provided extra information, but without major impact on management, in the following: the diagnosis of ventricular septal defects associated with other defects, of multiple ventricular septal defects, of anomalous pulmonary venous drainage, and of mild mitral regurgitation; the demonstration of site of coarctation, of stenotic or hypoplastic pulmonary artery branches, of unobstructed flow through a right atrial membrane, and of left ventricle to right atrium regurgitation; the assessment of the width of the duct and of flow through the patent foramen ovale in transposition and tricuspid atresia; the differentiation of pulmonary atresia from critical pulmonary stenosis and the measurement of maximum velocity of tricuspid regurgitation. CONCLUSIONS–Ideally all patients should undergo colour Doppler studies before cardiac surgery to ensure a more accurate diagnosis. However, since the additional information provided does not affect the management in most patients, machines without colour Doppler can provide a satisfactory service in paediatric cardiology centres in countries where resources are limited.